Multifunctional Delivery Systems for Peptide Nucleic Acids - Stefano Volpi; Umberto Cancelli; Martina Neri; Roberto Corradini (MDPI AG, 2020)
The number of applications of peptide nucleic acids (PNAs)-oligonucleotide analogs with a polyamide backbone-is continuously increasing in both in vitro and cellular systems and, parallel to this, delivery systems able to bring PNAs to their targets have been developed. This review is intended to give to the readers an overview on the available carriers for these oligonucleotide mimics, with a particular emphasis on newly developed multi-component- and multifunctional vehicles which boosted PNA research in recent years. The following approaches will be discussed: (a) conjugation with carrier molecules and peptides; (b) liposome formulations; (c) polymer nanoparticles; (d) inorganic porous nanoparticles; (e) carbon based nanocarriers; and (f) self-assembled and supramolecular systems. New therapeutic strategies enabled by the combination of PNA and proper delivery systems are discussed.